CRITERIA FOR DETERMINING THE GENRE OF HISTORICAL DRAMATIC WORKS AND THE DRAMA JALOLIDDIN MANGUBERDI - Mamatvaliev Mukhammad Kuymurodovich (International Journal of Literature and Language Studies, 2026)
ABSTRACT. This article provides a scientific and theoretical analysis of the role of the principle of sociality in defining the genre of a work of art on a historical theme. Specifically, the criteria for determining genres within the dramatic form are re-examined using the example of Makhsud Shaykhzoda's work